2020
DOI: 10.1097/md.0000000000023824
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of pasireotide for Cushing's disease

Abstract: Background: Cushing's disease (CD) is associated with increased risk of mortality, myocardial infarction, stroke, peptic ulcers, fractures and infections. The prevalence of CD is nearly 40 per million and higher in women than in men. When surgery has failed, is not feasible, or has been refused, pharmacotherapy can be considered a valuable option. Pasireotide is the first medical therapy officially approved for adult patients with CD. We will conduct a comprehensive systematic review and meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…In this context, pasireotide, a new second-generation SSA with the same affinity for SST2 as octreotide and lanreotide, but with a high affinity for SSTR1, SSTR3, and SSTR5, was approved by the FDA in 2014 [20,21]. Currently, pasireotide clinical use is focused on the treatment of growth hormone-secreting pituitary tumors and inhibiting corticotropin secretion from pituitary adenoma in patients with Cushing's disease [22,23]. A phase III clinical trial that used pasireotide in patients with TNE for six months showed no positive results, so it continues to be evaluated at present [19,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, pasireotide, a new second-generation SSA with the same affinity for SST2 as octreotide and lanreotide, but with a high affinity for SSTR1, SSTR3, and SSTR5, was approved by the FDA in 2014 [20,21]. Currently, pasireotide clinical use is focused on the treatment of growth hormone-secreting pituitary tumors and inhibiting corticotropin secretion from pituitary adenoma in patients with Cushing's disease [22,23]. A phase III clinical trial that used pasireotide in patients with TNE for six months showed no positive results, so it continues to be evaluated at present [19,24].…”
Section: Introductionmentioning
confidence: 99%